Sejarah Perkembangan Perpustakaan di Indonesia - Nurlidiawati, Nurlidiawati (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2014)
Libraries in Indonesia have been established since the time of Majapahit, which then, according to the ebb and flow of Indonesian history. The development of the library at the time marked by the royal library cultivated a more religious and feudalistic. In the Dutch colonial era, libraries had been used as a vehicle to perform the occupation. Receding rapidly developing libraries in Indonesia occurred at the time of the Japanese. Later, a few years after Indonesian Independence Proclamation, libraries in Indonesia were gradually developed. In the New Order Era, library development had become one of the sub development outlined in REPELITA (Indonesian Development Plans for the next 5 years).